2019
DOI: 10.3177/jnsv.65.470
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Myricetin against Cardiovascular Disease

Abstract: Cardiovascular disease (CVD) is the leading cause of death globally, except Africa, and poses a severe health burden worldwide. Both in vitro and in vivo studies have demonstrated the protective effects of myricetin for preventing CVD. For this review, we have assessed the literature from 2009 to 2019 at home and abroad to uncover the protective roles of myricetin for preventing CVD. Myricetin exhibits cardioprotective, anti-hypertensive, anti-atherosclerotic, anti-hyperglycemic, and anti-hyperlipidemic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…β-glucan (DG) is a bioactive polysaccharide composed of glucose monomers linked by 1–3, 1–4 or 1–6 glycosidic bonds ( Bai et al, 2019 ), which has gathered much attention due to its good biological activities such as regulation of immune ( Chethan et al, 2017 ), lowering blood glucose and serum cholesterol levels ( Ekström, Henningsson Bok, Sjöö, & Östman, 2017 ). Myricetin (MC, 3, 5, 7, 3′, 4′, 5′-OH), a class of hexahydroxy polyphenol, possesses excellent antioxidant activities ( Song et al, 2021 ), as well as anti-tumor ( Jiang, Zhu, Wang, & Yu, 2019 ) and cardiovascular-protective effects (L. Wang, Wu, Yang, & Dong, 2019 ). Previously, our lab has evidenced the formation of DG-MC complex with 35 % adsorption capacity of polyphenol.…”
Section: Introductionmentioning
confidence: 99%
“…β-glucan (DG) is a bioactive polysaccharide composed of glucose monomers linked by 1–3, 1–4 or 1–6 glycosidic bonds ( Bai et al, 2019 ), which has gathered much attention due to its good biological activities such as regulation of immune ( Chethan et al, 2017 ), lowering blood glucose and serum cholesterol levels ( Ekström, Henningsson Bok, Sjöö, & Östman, 2017 ). Myricetin (MC, 3, 5, 7, 3′, 4′, 5′-OH), a class of hexahydroxy polyphenol, possesses excellent antioxidant activities ( Song et al, 2021 ), as well as anti-tumor ( Jiang, Zhu, Wang, & Yu, 2019 ) and cardiovascular-protective effects (L. Wang, Wu, Yang, & Dong, 2019 ). Previously, our lab has evidenced the formation of DG-MC complex with 35 % adsorption capacity of polyphenol.…”
Section: Introductionmentioning
confidence: 99%
“…The lowest amount of caffeic acid was determined in the C 1 sample (2.70 ng ml −1 ) while the values in the other samples varied between 5.98 and 9.90 ng ml −1 . Myricetin is found in a variety of fruits and vegetables, nutrient‐enriched foods, especially grapes, and berries used in winemaking (Wang et al, 2019). Some studies reported that myricetin has antihypertensive and antitumor effects (Godse et al, 2010; Jiang et al, 2019; Stoll et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Among the detected 97 compounds selected from the natural products library, myricetin was found to significantly upregulate the expression of BACH2 and simultaneously suppress hypertrophic responses of ISO-stimulated cardiomyocytes. Myricetin is known to be a flavonoid compound widely present in plants and daily food ( Wang et al, 2019 ). It has been shown that myricetin has beneficial effects in a variety of cardiovascular diseases, including myocardial infarction, ischemia-reperfusion injury, heart failure and myocardial injury caused by lipopolysaccharide, endotoxin and ISO ( Cominacini et al, 2015 ; Gupta et al, 2020 ; Taheri et al, 2020 ; Zhang et al, 2020 ; Song et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%